Accepting our weaknesses and enjoying better relationships: An initial examination of self-security. (1st February 2017) - Huang, Alice B.; Berenbaum, Howard
Abstract: The present research introduces self-security, a new indicator of healthy self-evaluation. Self-security is defined as the open and nonjudgmental acceptance of one's own weaknesses. To assess self-security, we developed the Security of "I" Assessment (SofIA), a self-report questionnaire. Study 1′s ( N  = 195) exploratory factor analysis suggested a single-factor model that Study 2′s ( N  = 158) confirmatory factor analysis supported as providing good fit to the data. In Study 3 ( N  = 195), the SofIA demonstrated excellent test-retest reliability. Using the SofIA, Study 1 also explored self-security's correlates in a sample of 195 undergraduates, with 279 of their close others (family, long-term friends, and romantic partners) reporting on the quality of their relationships with the participants. Self-security was significantly associated, but not redundant with, other aspects of self-evaluation (e.g., self-esteem, self-compassion). Self-security was also associated with self-evaluative interpersonal traits and attachment style. Importantly, even after simultaneously accounting for other aspects of self-evaluation, self-security predicted relationship quality, as independently reported by the participants and their close others. Specifically, participants' greater self-security significantly predicted their experiencing less conflict and emotional distress and their close others' reporting more support received from the participants. Highlights: Self-security is a new construct defined as the acceptance of one's own weaknesses. Self-security is a facet of self-evaluation linked to healthy interpersonal traits. Self-security is associated with secure attachment style and relationship quality. Self-security is associated with relationship quality reported by close others. Associations with self-security remain after accounting for similar constructs.